Efisiensi Pewarnaan Batik Tulis dengan Waterglass Menggunakan Roll Saving Pada Kelompok Pengrajin Batik Desa Tampo Kecamatan Cluring Kabupaten Banyuwangi - Asmuni, Hadiqoh (MOMENTUM : Jurnal Sosial dan Keagamaan, 2021)
Batik is typical Indonesian cloths. From the beginning of the emergence the banyuwangi batik, several motiv haves emergate philoshopical meaning. Batik is increasingly rapid in the devepment of banyuwangi. As evidenced by the increasing number of batik crafment. This proves the typical banyuwangi batik has salling value of demand by many people. Howover , the production of batik crafment banyuwangi not be maximalized due to the limit skill to using waterglasses manually. So that is has not be able to meet market demend optimally. This is felt by crafment batik in the tampo village. Tampo is batik areas because many batik crafment have produce with uniqe motiv. As solution of produce batik from najikha batik is collaborate in conducting waterglass use skill training. Empowerment written batik crafment focus on najiha’s problem; 1) using of waterglass wich wasteful; 2) the color of written batik is not consistent, the brightness level is not same; 3) need for color lock technology and tool; 4) it is necessary to transfer the coloring technology using waterglass to najiha’s group ; 5) need for trining and assistance to market banyuwangi written batik nationally; 6)najiha’s group does written batik catalog not yet: 7) the book keeping absence. The PKM team conducets trining for crafmen with result; 1) creation of roll saving tools; 2) 85% Najiha’s employes are able use the role saving tool well; 3) 85% of the color written batik has increased quality, brightness and durability; 4) 75% increase marketing by najiha batik; 5) najiha have batik catalog; 6)najiha have book keeping through exel; 7) significant increase in sale turn over by 65%. Method and stages in the application of technology: starting from the stage of the situation analysis, the identification of the problem, the used in effective waterglass. The result of PKM in the form of roll saving tool were given to najiha batik, who then helped market to product by creating written batik catalog (web and social media)